2012
DOI: 10.1007/s12035-012-8292-7
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Enhance Nerve Regeneration after Sciatic Nerve Injury in Rats

Abstract: With the development of tissue engineering and the shortage of autologous nerve grafts in nerve reconstruction, cell transplantation in a conduit is an alternative strategy to improve nerve regeneration. The present study evaluated the effects and mechanism of brain-derived neural stem cells (NSCs) on sciatic nerve injury in rats. At the transection of the sciatic nerve, a 10-mm gap between the nerve stumps was bridged with a silicon conduit filled with 5 × 10(5) NSCs. In control experiments, the conduit was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 36 publications
1
33
0
2
Order By: Relevance
“…NGF, composed of 118 amino acid residues (Angeletti et al, 1971) has been discovered in the 1950s (Levi-Montalcini and Hamburger, 1951; Levi-Montalcini, 1952; Cohen et al, 1954; Levi-Montalcini and Booker, 1960); it displays multiple physiological actions in the central nervous system, showing neurotrophic effects and resulting critical for the neurite outgrowth and survival and maintenance of neurons (Hu et al, 2005; Tucker et al, 2008; Xu et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…NGF, composed of 118 amino acid residues (Angeletti et al, 1971) has been discovered in the 1950s (Levi-Montalcini and Hamburger, 1951; Levi-Montalcini, 1952; Cohen et al, 1954; Levi-Montalcini and Booker, 1960); it displays multiple physiological actions in the central nervous system, showing neurotrophic effects and resulting critical for the neurite outgrowth and survival and maintenance of neurons (Hu et al, 2005; Tucker et al, 2008; Xu et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…To date, several methods have been developed to improve the efficacy of nerve conduits by accelerating nerve regeneration and bridging longer nerve gaps [Johnson et al, 2013;Carriel et al, 2014;Li et al, 2014]. In particular, transplantation of supportive cells such as Schwann cells, neural crest stem cells and bone marrowderived mesenchymal stem cells within nerve conduits enhances the repair of long nerve defects [Mosahebi et al, 2002;Xu et al, 2012;Hsu et al, 2013;Hu et al, 2013;Li et al, 2014]. The induced pluripotent stem cell (iPSc) represents an attractive source of cells that are potentially useful for nerve conduit support [Takahashi and Yamanaka, 2006;Xu et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…NGF possesses neurotrophic effects and is critical for the neurite outgrowth and survival and maintenance of neurons. Studies, in vitro and in vivo , have shown that NGF stimulates neurite outgrowth and axonal branching and extension [1820]. Most importantly, NGF has strong antiapoptotic effect and, with deprivation of NGF, neurons exhibit a series of morphological changes and eventually undergo apoptosis [21].…”
Section: Nerve Growth Factor Receptors and Their Signaling Pathwaysmentioning
confidence: 99%
“…PI3K is activated and recruited to the plasma membrane and leads to the production of phosphoinositide 3,4,5-trisphosphate and membrane translocation of the serine/threonine-protein kinases Akt and Akt activation [20]. Although there are other downstream targets of PI3K, the PI3K/Akt signaling pathway is particularly important for neuronal survival and the synthesis of many new cellular proteins.…”
Section: Nerve Growth Factor Receptors and Their Signaling Pathwaysmentioning
confidence: 99%